Penggunaan Internet, Perkembangan Sektor Keuangan dan Pertumbuhan Ekonomi: Data Panel Kabupaten Kota di Aceh - Hajriyanti, Rahmi; Ester, Ester (Lembaga KITA, 2019)
This study aims to analyze the effect of internet use and bank lending on Aceh's economic growth. The data used are secondary in the form of panel data of 15 city districts in Aceh during the period 2010-2017. The analysis model used is Johanson Co-integration, Panel Vector Autoregressive (PVAR) and Granger Causality Test. The study found that there is no long-term relationship between internet use, bank lending, and economic growth. Bank credit has a positive and significant effect on economic growth. The use of the internet has a positive and significant impact on bank lending but does not affect economic growth. Furthermore, economic growth and bank lending have a positive and significant effect on internet usage. Granger causality test results indicate that there is a one-way causality from bank credit to economic growth and internet use.Keywords: Economic Growth, Internet Use, Bank Credit, and Panel Vector Autoregressive